No Child Left Behind : past, present, and future - Hayes, William, 1938- (Rowman & Littlefield Education, 2008)
While few would quarrel with the goal of the No Child Left Behind legislation, the nation is badly divided over whether the law is having a positive effect on our schools. At the same time, it is also true that most Americans, including many professionaleducators, have only a limited understanding of the content and scope of the legislation. As we are currently engaged in a national debate about the future role of the federal government in the field of education, it is essential that people become betterinformed about the history, content, and results of No Child Left Behind. This book is a v.